2018
DOI: 10.1371/journal.pone.0209616
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported free-living physical activity and executive control in young adults

Abstract: To what extent do our free-living physical activity (PA) levels impact our cognition? For example, if we engage in more intense PA from one week to the next, does this have a corresponding influence on cognitive performance? Across three studies, young adults completed a validated self-report questionnaire (the International Physical Activity Questionnaire, or IPAQ) assessing their involvement in PA at low, moderate, and vigorous intensities over the past week, as well as computer-based measures of executive c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 87 publications
(143 reference statements)
1
8
0
Order By: Relevance
“…Hillman et al (2006) reported a faster reaction time associated with PA in subjects between 15 and 71; this result was independent of age. On the other hand, a recent study, carried out in university students, of a similar age range as our population, that evaluated the relationship between PA, reported by the IPAQ (long version), and executive function, found no association (Ho et al, 2018). Despite a similar design and target population, there are several methodological differences.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Hillman et al (2006) reported a faster reaction time associated with PA in subjects between 15 and 71; this result was independent of age. On the other hand, a recent study, carried out in university students, of a similar age range as our population, that evaluated the relationship between PA, reported by the IPAQ (long version), and executive function, found no association (Ho et al, 2018). Despite a similar design and target population, there are several methodological differences.…”
Section: Discussionmentioning
confidence: 57%
“…First, the instrument used to evaluate the executive function differed between studies. Ho et al (2018) used the flanker task-a task related to attention and inhibition that has been shown to activate similar brain regions in functional MRI as the Stroop test, such as the anterior cingular cortex (APP) and left prefrontal cortex (lPFC; Fan et al, 2003). Despite the similarity of the two neurocognitive tests, a study reported that the time needed to resolve the response conflict in Stroop's task did not predict the time needed to resolve the response conflict in the flanker task, and therefore, the interference scores between the two tasks were not correlated.…”
Section: Discussionmentioning
confidence: 99%
“…Original analysis of these data sets found no evidence to support that PA over the previous 7 days impacts basic RT on executive control tasks (Ho et al, 2018).…”
Section: Resultsmentioning
confidence: 91%
“…This article utilizes a dataset previously analyzed and reported (Ho et al, 2018). For further information regarding the purpose of the studies, their findings, and the implications consult Ho et al (2018).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation